Genetic manipulation of Staphylococci – Breaking through the barrier. - Monk, Ian R.; Foster, Timothy J. (Frontiers in Cellular and Infection Microbiology, 2012)
Most strains of Staphylococcus aureus and Staphylococcus epidermidis possess a strong restriction barrier that hinders exchange of DNA. Recently, major advances have been made in identifying and characterizing the restriction-modification systems involved. In particular a novel type IV restriction enzyme that recognizes cytosine methylated DNA has been shown to be the major barrier to transfer of plasmid DNA from Escherichia coli into S. aureus and S. epidermidis. One or sometimes two type I restriction-modification systems provide an additional barrier. Here we review the recent advances in understanding of restriction systems in staphylococci and highlight how this has been exploited to improve our ability to manipulate genetically previously untransformable strains.